Derivation of optical solitons of dimensionless Fokas-Lenells equation with perturbation term using Sardar sub-equation method - Cinar, Melih; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (SPRINGER, 2022)
This paper presents an investigation of soliton solutions for the perturbed Fokas-Lenells (pFL) equation, which has a vital role in optics, using Sardar sub-equation method. The equation models the propagation of ultrashort light pulses in optical fibers. Using appropriate wave transformation, the pFL equation is reduced to a nonlinear ordinary differential equation (NLODE). The solutions of this NLODE equation are assumed to be in the suggested form by the Sardar sub-equation method. Hence, an algebraic equation system is obtained by substituting the trial solution and their necessary derivatives into the NLODE. After finding the unknowns in the system, the soliton solutions of the perturbed Fokas-Lenells equation are extracted. The method produces various kinds of solitons such as dark, periodic, singular periodic, combined bright-dark. To show physical representations of the solitons, 2D, 3D and contour plots of the solutions are demonstrated via computer algebraic systems. It is expected that derived solutions may be useful for future works in various fields of science, especially optics and so, it may contribute to the optic fiber industry.
Keywords: Fokas-Lenells equation; Optical fiber; Sardar sub-equation method; Solitons; NUMERICAL-SIMULATION; MODEL; Engineering; Physics; Optics